Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Knowledge Management pada Perusahaan Pengguna Sap - Dian J. Bantam; Dimas A. Nugraha; Nailis Sa'adah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2016)
Â System Applications and Products (SAP) is system of information that integreting and involving many fungtions. Many organizations use SAP in Indonesian, but some of people don't know about the system. This research measured impact of organizational commitment and organizational culture on knowledge management in SAP company. The participant of this study is 32 employees that including 2 companies in Yogyakarta that using SAP. Research used quantitative approach with the help of multiple regression analysis to show impact of organizational culture and organizational commitment on knowledge management. The result showed organizational culture and organizational commitment giving impact to knowledge management (p=0.007, p<0.05; R=0.287, R=28.7%). So, hipothesis of this research is received, that there is impact of organizational culture and organizational commitment on knowledge management in company that using SAP.Â Keywords: Knowledge management (KM), Organizational Culture, Organizational Commitment, SystemApplication and Product (SAP).